The Influence of Customer Relationship Management (CRM) and Brand Image on NCT Dream Album Purchase Decisions - Listyanti, Nur Utami (Institute of Computer Science (IOCS), 2024)
This quantitative research aims to determine the influence of customer relationship management and brand image on purchasing decisions for NCT Dream products. Researchers used a sample of 100 NCT Dream fan respondents aged over 17 years and domiciled in DKI Jakarta who had ever purchased NCT Dream merchandise or albums. The sampling technique uses purposive sampling and snowball sampling. The data analysis used is the t test using the SmartPLS application. Based on the research results, it can be concluded that customer relationship management has a positive and significant effect on purchasing decisions. Meanwhile, the other independent variable, namely brand image, does not have a positive and significant effect on purchasing decisions.